UNVEILING OSTEOPETROSIS: A CASE STUDY WITH ORAL AND RADIOGRAPHIC FINDINGS - Petkov, Trisha (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Osteopetrosis, often referred to as "marble bone disease" or "Albers-Schönberg disease," is a rare hereditary skeletal disorder characterized by a substantial increase in bone density and a reduction in marrow spaces. This condition results from a defect in bone remodeling due to the impaired functioning of osteoclasts, leading to a diminished bone turnover. Osteopetrosis manifests in three primary clinical forms, including a severe malignant infantile autosomal recessive form, an intermediate mild autosomal recessive form, and a benign/adult osteopetrosis with autosomal dominant inheritance. While the latter exhibits fewer symptoms, the first two types have a dismal prognosis, typically manifesting within the first decade of life and leading to early mortality. Infants affected by osteopetrosis may experience a range of clinical symptoms, including impaired hematopoiesis, hepatosplenomegaly, macrocephaly, visual impairment, bone fractures, and hypocalcemia. Although rare, involvement of the endocrine system, except for secondary hyperparathyroidism, has also been reported.